Studi Kelayakan Pengembangan Pasar Hewan di Kabupaten Bekasi - Rahmat Nuryono (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2012)
Animal/Cattle market which is the the place where the breeder, trader, and collector between regions conduct animal buying and selling transaction, also has function to do animal trading that is traded and applies transparant mechanism transaction with more open traded method like auction. The Application of trading transaction by auction will be able to give conducive appeal for production escalation. In the effort to increase market access and streamline animal market system, it needs feasibility study for animal market development so that animal market management as market utility and strengthening institutional farmer can give optimal benefit for the perpetrator marketing and consumer as expected. The development of animal market is expected to give positive impact toward the increasing of labor opportunity, income per capita, saving exchange, the increasing of production facility that can support the establishment of new industry, top to below (backward and forward linkage), such as the emergence of industry that uses slaughtering product or the side rsult of animal market like food industry ( canned meat, sausage, meat ball, etc), animal skin industry, bone processing, animal feed, fertilizer, and etc